Functionalized graphene – poly(vinyl alcohol) nanocomposites: Physical and dielectric properties - G. C. Psarras; I. Tantis; D. Tasis (eXPRESS Polymer Letters)
Chemically derivatized graphene/poly(vinyl alcohol) (PVA) nanocomposites were successfully fabricated by combination of solution processing and compression molding. SEM imaging combined with XRD measurements revealed that graphene platelets were fully incorporated into the polymer matrix after their chemical modification through adsorption of amphiphilic copolymer. The chemical functionalities onto the graphitic surface prevented particle aggregation and provided compatibility with the polymer matrix. Thermogravimetric analysis demonstrated enhanced thermal stability for the composites containing modified graphenes at loading above 1 wt%. Differential scanning calorimetry thermograms showed that graphene nanoplatelets induced the crystallization of matrix with optimum loading at 2 wt%. Dielectric spectroscopy measurements showed enhanced electrical permittivity for the graphene oxide/PVA system, compared to the one of graphene/copolymer/PVA. This could be attributed to the formation of an insulating coating between graphite inclusions and PVA because of the presence of the copolymer.